Rola ćwiczeń tłumaczeniowych na lekcjach języka obcego - Kubacki, Artur Dariusz (Neofilolog, 2010)
The aim of the article is to present the role of translation exercises during foreign language lessons. On the basis of the questionnaire research conducted at a secondary school, the author tries to prove that those scholars who claim that translation exercises should not be used during foreign language lessons are wrong. Although the grammar translation method, which treated translation as a precondition for mastering a foreign language, was harshly criticised, it is now clear that the mother tongue – and hence translation – plays a significant part in the foreign language acquisition process. My empirical research also confirms that teachers often return to translation exercises during foreign language lessons.